2014
DOI: 10.1186/1476-4598-13-240
|View full text |Cite
|
Sign up to set email alerts
|

Pim-1 kinase is a target of miR-486-5p and eukaryotic translation initiation factor 4E, and plays a critical role in lung cancer

Abstract: BackgroundPim-1 kinase is a proto-oncogene and its dysregulation contributes to tumorigenesis and progression of a variety of malignancies. Pim-1 was suggested as a therapeutic target of cancers. The functional relevance of Pim-1 and the mechanism underlying its dysregulation in lung tumorigenesis remained unclear. This study aimed to investigate if Pim-1 has important functions in non-small-cell lung cancer (NSCLC) by: 1) evaluating the clinicopathologic significance of Pim-1 through analysing its expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
45
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 31 publications
4
45
1
Order By: Relevance
“…miR-486 is located on one of the most frequent genomic rearrangement regions, chromosome 8p11.21, which contains potential tumor-suppressor genes in lung tumorigenesis. Recent findings have shown miR-486-5p plays a critical role in breast and lung cancer by targeted PIM-1 (41,42). The results from the present study are consistent with those of previous findings, suggesting that miR-486-5p is a potential tumor suppressor in carcinogenesis.…”
Section: Patients With Lowersupporting
confidence: 83%
“…miR-486 is located on one of the most frequent genomic rearrangement regions, chromosome 8p11.21, which contains potential tumor-suppressor genes in lung tumorigenesis. Recent findings have shown miR-486-5p plays a critical role in breast and lung cancer by targeted PIM-1 (41,42). The results from the present study are consistent with those of previous findings, suggesting that miR-486-5p is a potential tumor suppressor in carcinogenesis.…”
Section: Patients With Lowersupporting
confidence: 83%
“…1A). Although miR-486-5p down-regulation and its effects in promoting lung carcinogenesis have been previously reported [3,810], the mechanism of repression is unknown. MicroRNAome analysis of NSCLC cell lines treated with vehicle or DAC as described [33] showed that DAC treatment increased miR-486-5p expression in 5/10 cell lines with lowest expression by 2 to 8-fold (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…MiR-486-5p is a tumor-suppressor miR that is often down-regulated across multiple malignancies including lung [3,4], gastric [5], pancreatic [6], and other [7] cancers. In vitro and laboratory animal based gain- or loss-of-function studies on miR-486-5p have confirmed its role in suppressing the growth of lung cancer [810]. Reduced miR-486-5p expression strongly contribute to lung cancer progression while recent studies showed that it could be reliably detected in easily accessible samples such as serum and sputum indicating its potential as a prognostic biomarker.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 microRNAs miR-451a and miR-144 have yet to be identified in any non-neoplastic cell type, yet they repeatedly are assigned non-RBC functionality due to tissue level data being confused for cell level expression data (Tables 1 and 2). 12-17 miR-486 is also abundant in platelets, but neither RBC nor platelet expression justifies its assigned role in a variety of disease states in which it is unlikely to participate. 18,19 Thus it is important to identify the cellular source of a tissue-level microRNA signature, which can be done by checking known datasets, 5,20 obtaining cell-specific data from the Sequence Read Archive or Gene Expression Omnibus, or measuring the microRNA by qPCR or northern blot in a cell type of interest.…”
mentioning
confidence: 99%